An Exploratory Factor Analysis of Lean Construction Elements Reflecting Project Management Performance among Local Construction Enterprises - Wattana, Kanop; Koschanin, Jensak; Luanghan, Itsariyaporn; Buranajarukorn, Panu; Jampachaisri, Katechan (Science and Engineering Connect, 2025)
Background and Objectives: The construction industry remains a pivotal sector in national development, yet it frequently faces systemic inefficiencies, including project delays, cost overruns, and materials waste. These challenges are especially pronounced among local construction enterprises, which often operate with limited resources, simple organizational structures, and minimal access to modern technologies. The adoption of Lean Construction Concepts (LCC) has gained increasing attention as a viable solution to address the issues. Lean construction emphasizes minimizing waste, while maximizing value creation, aiming to optimize construction processes and improve labor productivity throughout project execution. Despite the growing global adoption of lean methodologies, their implementation in Thailand’s local construction sector remains underexplored, particularly regarding how various lean components influence overall project management performance. The main objective of this study was to identify and classify the structural elements of lean construction that significantly affect project management efficiency within local construction enterprises in Thailand. This research aims to bridge the existing knowledge gap and provide a systematic framework tailored to the unique challenges faced by such enterprises. Methodology: The study adopted a quantitative research methodology, using Exploratory Factor Analysis (EFA) to uncover the underlying structure of lean construction elements that influence project management performance. Data were collected through a structured questionnaire survey distributed to local construction professionals across Thailand. A total of 115 valid responses were obtained, satisfying statistical adequacy tests. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was found to be 0.845, while Bartlett’s test of sphericity yielded a p-value < 0.001, indicating that the dataset was suitable for factor analysis. Items with a Measure of Sampling Adequacy (MSA) below 0.50 were excluded to enhance model accuracy. Reliability was confirmed through Cronbach’s alpha values of 0.927 and 0.938 for the factor groups and the overall instrument, respectively, indicating high internal consistency. Main Results: The EFA results reveal six key components comprising 31 variables that collectively explained 59.70% of the total variance. The identified factors are: (1) cost and quality, emphasizing process improvement, elimination of redundancy, and resource optimization; (2) strategy and planning, underscoring the importance of effective project scheduling, budget adherence, and personnel management; (3) safety, highlighting the implementation of safety measures and proper use of personal protective equipment to prevent accidents and health risks; (4) people and processing, which focus on reducing task duration, enhancing labor efficiency, and streamlining procurement and logistics; (5) waste, emphasizing reduction of materials waste and promotion of 5S principles for environmental and operational efficiency; and (6) health and accident, which relate to monitoring accident rates, ensuring health standards, and minimizing disruptions caused by workplace incidents. The variable with the highest factor loading (0.818) pertains to materials waste reduction, reflecting its critical importance in resource-constrained local enterprises. Conclusions: The study successfully establishes a comprehensive framework for understanding how lean construction elements impact project management performance among local construction enterprises in Thailand. The six-factor model provides empirical support for the strategic implementation of lean principles, illustrating their effectiveness in enhancing cost efficiency, process reliability, safety performance, and environmental sustainability. These findings emphasize the importance of tailored lean applications that consider the unique operational characteristics of local firms, such as capital constraints and labor management challenges. The research contributes to the broader field of lean construction by extending its practical relevance to developing economies, where localized adaptation is crucial for successful implementation. Practical Application: The study offers practical insights to local construction practitioners, project managers, and policymakers seeking to improve project outcomes through lean methodologies. By categorizing the essential elements of lean construction into six actionable components, the findings provide a structured implementation roadmap for local enterprises. Project managers can use these insights to prioritize lean strategies that directly enhance productivity and efficiency, including waste reduction, strategic planning, and safety compliance. Moreover, the research lays the groundwork for developing training programs, organizational policies, and performance monitoring tools aligned with lean construction principles. Future research should expand this model to examine its applicability in large-scale infrastructure projects and conduct comparative analyses with international case studies. Such extensions will foster the creation of globally informed best practices and reinforce the long-term sustainability and competitiveness of Thailand’s construction sector.